2018
DOI: 10.1096/fj.201800509r
|View full text |Cite
|
Sign up to set email alerts
|

Novel noncanonical regulation of soluble VEGF/VEGFR2 signaling by mechanosensitive ion channel TRPV4

Abstract: VEGF signaling via VEGF receptor-2 (VEGFR2) is a major regulator of endothelial cell (EC) functions, including angiogenesis. Although most studies of angiogenesis focus on soluble VEGF signaling, mechanical signaling also plays a critical role. Here, we examined the consequence of disruption of mechanical signaling on soluble signaling pathways. Specifically, we observed that small interfering RNA (siRNA) knockdown of a mechanosensitive ion channel, transient receptor potential vanilloid 4 (TRPV4), significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…Further, TRPV4-mediated calcium influx was significantly attenuated in these cells. Downregulation of TRPV4 has been shown to activate VEGF/VEGFR2 pathway via Rho kinase/YAP (Kanugula et al, 2019), and indeed, we found that TCM treatment significantly reduced perinuclear VEGFR2 suggesting activation of VEGFR2 in hTEC (Manickam et al, 2011;Wang et al, 2017). Further, pharmacological inhibition of Rho kinase was able to normalize abnormal angiogenesis exhibited by hTEC.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Further, TRPV4-mediated calcium influx was significantly attenuated in these cells. Downregulation of TRPV4 has been shown to activate VEGF/VEGFR2 pathway via Rho kinase/YAP (Kanugula et al, 2019), and indeed, we found that TCM treatment significantly reduced perinuclear VEGFR2 suggesting activation of VEGFR2 in hTEC (Manickam et al, 2011;Wang et al, 2017). Further, pharmacological inhibition of Rho kinase was able to normalize abnormal angiogenesis exhibited by hTEC.…”
Section: Discussionsupporting
confidence: 59%
“…Further, calcium imaging revealed that TRPV4-mediated calcium influx in response to the specific agonist GSK1016790A, was significantly lower in hTEC (p ≤ 0.0001) compared to hNEC (Figures 2C,D). We next asked if the reduction in TRPV4 altered vascular endothelial growth factor receptor 2 (VEGFR2) or Rho/Rho kinase pathways in hTEC, which we have previously shown to be activated in TRPV4 null (TRPV4KO) or TRPV4 siRNA knocked down EC (Kanugula et al, 2019). Indeed, immunostaining revealed a significant reduction of perinuclear VEGFR2 levels in hTEC compared to hNEC (p ≤ 0.0001) (Figures 3A,B).…”
Section: Tumor Cell Conditioned Media Induces Hnec Transformation To mentioning
confidence: 93%
See 1 more Smart Citation
“…Early work demonstrated that mechanical stimulation of TRPV4 by cyclic strain induced bovine capillary endothelial cells to realign perpendicular to the direction of the strain upon PI3K-dependent β1 integrin recruitment, stress fiber and focal adhesion rearrangement (Thodeti et al, 2009). Interestingly, the same group recently demonstrated that genetic silencing of TRPV4 increased the cell surface expression and phosphorylation at Y1175 of VEGFR2 in HMECs, thereby stimulating VEGF-induced migration (Kanugula et al, 2019). The emerging role played by TRPV4 in angiogenesis was further corroborated by Hatano et al (2013), who found that TRPV4 activation by 4α-PDD induced proliferation in human brain capillary endothelial cells.…”
Section: Trpv4 In Angiogenesismentioning
confidence: 99%
“…Specifically, the TRP family member, TRPV4, is a ubiquitously-expressed, plasma membrane-based, calcium-permeable channel that is sensitized and activated by both chemical [5,6-Epoxyeicosatrienoic acid (EET), 4 alphaphorbol 12,13-didecanoate (4-αPDD)] and physical stimuli (temperature, stretch, and hypotonicity) (40)(41)(42)(43). TRPV4 can initiate intracellular, celltype and context-specific signals that depend on local increases in intracellular calcium which could act as a second messenger, and/or induce heterodimerization with other channels, activate kinases, and/or directly interact with cytoskeletal proteins via intracellular amino-(NH 2 ) and carboxy-(COOH) terminal tails (44)(45)(46)(47).…”
Section: The Trpv4 Channel and Mechanobiology Of The Lungmentioning
confidence: 99%